Utilization of Funds and the Mentoring Process of PNM Mekaar Syariah in Community Economic Empowerment in Panton Teunom Village, Aceh Jaya - Rasmita; Musfiana; Amrusi; Rahmilia Hadiyani; Aidil Akbar (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
The scarcity of capital and the suboptimal welfare of underprivileged women necessitate the reinforcement of micro-enterprises, a condition further exacerbated by the diversion of financing funds toward consumptive needs and the inadequacy of business development mentoring modules in Panton Teunom Village, Aceh Jaya. Consequently, this study aims to examine the utilization of financing and the efficacy of the mentoring process within the PNM Mekaar Syariah program in accelerating the economic empowerment of this demographic. Employing a descriptive qualitative approach, data were acquired from six purposively selected informants through structured interviews and documentation. The analytical framework utilized interactive model stages encompassing data reduction, data display, and conclusion drawing. The findings reveal that the majority of the financial allocations were effectively utilized as capital supplements, significantly optimizing inventory capacity, business expansion, and income generation. Furthermore, weekly group mentoring demonstrably fortified disciplinary practices, managerial literacy, and entrepreneurial autonomy, notwithstanding the persistence of consumptive constraints. Ultimately, the program's success in consolidating women's economic resilience dictates a pressing need for policymakers to optimize the oversight of financial literacy and integrate an advanced business incubation curriculum, thereby ensuring the long-term sustainability of micro-enterprises.